2017
DOI: 10.4196/kjpp.2017.21.4.415
|View full text |Cite
|
Sign up to set email alerts
|

Escitalopram, a selective serotonin reuptake inhibitor, inhibits voltage-dependent K+channels in coronary arterial smooth muscle cells

Abstract: We investigated the inhibitory effect of escitalopram, a selective serotonin reuptake inhibitor (SSRI), on voltage-dependent K+ (Kv) channels in freshly separated from rabbit coronary arterial smooth muscle cells. The application of escitalopram rapidly inhibited vascular Kv channels. Kv currents were progressively inhibited by an increase in the concentrations of escitalopram, suggesting that escitalopram inhibited vascular Kv currents in a concentration-dependent manner. The IC50 value and Hill coefficient f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…In particular, augmentation of Notch1 activity may play a role in the effects seen in our disease models. Sertraline (25) and escitalopram (26) have been shown to inhibit voltage-dependent K+ channel activity in smooth muscle cells, suggesting another potential mechanism to be investigated in a future study. It is notable that serotonin treatment did not rescue the drpr-deficient flies, suggesting that the mechanism of action of sertraline in this context is independent of effects on serotonin activity.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, augmentation of Notch1 activity may play a role in the effects seen in our disease models. Sertraline (25) and escitalopram (26) have been shown to inhibit voltage-dependent K+ channel activity in smooth muscle cells, suggesting another potential mechanism to be investigated in a future study. It is notable that serotonin treatment did not rescue the drpr-deficient flies, suggesting that the mechanism of action of sertraline in this context is independent of effects on serotonin activity.…”
Section: Discussionmentioning
confidence: 99%
“…The studies conducted on animal models have shown that fluoxetine causes dilatation of cerebral arterioles and skeletal muscle arterioles, as well as inhibition of the potassium‐induced contraction of the isolated uterine artery . A group of authors from South Korea showed that escitalopram, sertraline, and fluvoxamine cause dose‐dependent inhibition of voltage‐dependent potassium channels and consequent vasoconstriction in coronary arterial smooth muscle cells of rabbits. On the other hand, in the same studies paroxetine did not affect the contractility of coronary smooth muscle cells.…”
Section: Discussionmentioning
confidence: 99%
“…'vreme' = time in seconds shown that fluoxetine causes dilatation of cerebral arterioles 15 and skeletal muscle arterioles, 16 as well as inhibition of the potassiuminduced contraction of the isolated uterine artery. 16 A group of authors from South Korea showed that escitalopram, 10 with the current state of knowledge. Paroxetine was found to have contractile effects on guinea-pig urethra, while other SSRIs did not, 17 and citalopram was the only SSRI that did not inhibit acetylcholineinduced contractions of guinea-pig urinary bladder, 18 suggesting outstanding pro-contractile effect of these two drugs on smooth muscles; but we cannot progress further from these observations when trying to understand selectivity of their action on contractility of the fallopian tube ampulla and isthmus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, the adverse effects of some drugs on vascular Kv channels should be investigated to avoid misinterpretation of clinical/experimental data regarding vascular function. To date, various drugs and chemicals have been reported to inhibit vascular Kv channels independently of their intrinsic functions [ 22 23 ]. Our group recently reported the direct effect of amiodarone, a class III antiarrhythmic drug, on vascular Kv channels using coronary arterial smooth muscle cells [ 24 ].…”
Section: Discussionmentioning
confidence: 99%